Brazilian women living in Portugal: work and quality of life - Oliveira, Eliany Nazaré; Matias, Manuelle Maria Marques; Félix, Tamires Alexandre; Cavalcante, Maria Michele Bispo; Lopes, Roberlândia Evangelista; Neto, Félix (Saúde e Sociedade, 2019)
This article is organized around the axes migratory process, work, and quality of life. Two objectives were outlined: characterizing the sociodemographic aspects of Brazilian immigrant women in Portugal; and analyzing their situation and characteristics of work and quality of life. The study started from two working hypotheses: the first on the relation between unemployment and low quality of life; and the second on the relation between high workload and low quality of life of immigrant women. Cross-sectional study conducted from July to September 2016, in Portugal, with 682 Brazilian immigrant women over 18 years of age who lived in the country for more than 3 months. The instruments used were a socio-demographic questionnaire and the questionnaire ‘Medical Outcomes Study 36-Item Short-Form Health Survey’ (SF-36). The results showed a predominance of women in the age group from 18 to 38 years; married or living in a marriage-like relationship; with formal education mostly at the graduate level; with child(ren); and living in a family unit. The first study hypothesis was confirmed and the second study hypothesis was refuted.